The Impact of Lexicographical Work on Language Use: The Case of Shona Monolingual Dictionaries in Zimbabwe - Nyota, S.; Mapara, J. (Lexikos, 2007)
Abstract: This article examines the impact of current lexicographical work in Zimbabwe on some sectors of Shona language use, namely education, media, medicine and local government. It looks specifically at Shona monolingual lexicographical projects completed by the African Languages Research Institute (ALRI), successor to the African Languages Lexical Project (ALLEX). It analyses how users of Shona in these particular sectors are responding to the different lexicographical products published by ALRI. The article maintains that Shona monolingual lexicography has resulted in language raising and awareness. It has also led to term creation and has contributed towards standardisation of the language. Shona has furthermore gained the abstractive power it needs to explain its own and other concepts. All these have caused diglossia leakage from Low (L) Shona to High (H) Shona in some areas of Shona language usage. The overall effect is that Shona is now used in some formal sectors such as the above-mentioned ones which previously were the preserve of English in Zimbabwe.Keywords: MONOLINGUAL LEXICOGRAPHY, GENERAL DICTIONARIES, SPECIALISED DICTIONARIES, STANDARDISATION, LANGUAGE RAISING, LANGUAGE AWARENESS, LANGUAGE USE, SLCA, ALLEX, ALRIOpsomming: Die invloed van leksikografiese werk op taalgebruik: Die geval van Sjona- eentalige woordeboeke in Zimbabwe. Hierdie artikel ondersoek die uitwerking van die huidige leksikografiese werk in Zimbabwe op sekere sektore van Sjonataal-gebruik, naamlik opvoeding, media, geneeskunde en plaaslike regering. Dit kyk spesifiek na Sjona- eentalige leksikografiese projekte wat deur die African Languages Research Institute (ALRI), opvolger van die African Languages Lexical Projects (ALLEX), voltooi is. Dit ontleed hoe gebrui-kers van Sjona in hierdie besondere sektore reageer op die verskillende leksikografiese produkte wat ALRI gepubliseer het. Die artikel voer aan dat Sjona- eentalige leksikografie taalverhoging en -bewustheid tot gevolg gehad het. Dit het ook gelei tot termskepping en het bygedra tot die stan-daardisering van die taal. Sjona het verder die abstraherende vermoë verkry wat dit nodig het om sy eie en ander konsepte te verduidelik. Dit alles het diglossielekkasie van Lae (L) Sjona na Hoë (H) Sjona op sekere gebiede van Sjonataalgebruik veroorsaak. Die algehele uitwerking is dat Sjona tans gebruik word in 'n aantal formele sektore soos die bogenoemdes wat vroeër die alleengebied van Engels in Zimbabwe was.Sleutelwoorde: EENTALIGE LEKSIKOGRAFIE, ALGEMENE WOORDEBOEKE, GESPE-SIALISEERDE WOORDEBOEKE, STANDAARDISERING, TAALVERHOGING, TAALBEWUST-HEID, TAALGEBRUIK, SLCA, ALLEX, ALRI